GENETIC POLYMORPHISMS OF CSN3 GENE AND ITS EFFECT ON SOME PRODUCTION TRAITS - Fadhil, I. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Kappa-Casein gene (CSN3) polymorphisms were investigated in one breed of sheep (Awassi) reared in Babylon City. Genomic DNA was extracted from blood of 51 samples of Awassi ewe by using one primer. The primer of PCR were sequenced and prepared by Integrated DNA Technologies Company. PCR productions were loaded on gel electrophoresis. The polymorphism of kappa - casein gene was genotyped by Hindlll restriction enzyme (TAKARA), PCR products, Ethidium bromide and 2.5% Agarose gel in horizontal Medi Bio Rad electrophoresis with 0.5 x TBE (100 V. for 60 min.) were loaded to identify of results using Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) analysis. The present paper revealed three genetic patterns (AA, AB and BB) with two alleles (A and B). The gene frequency for A allele was record high percentage than the other allele (B). The statistical analysis of CSN3 patterns was indicated no significance different on parameters of milk components, while the results appeared positive influence of AB pattern on milk components inside the breed, that is confirm high in heterozygous genotype production (AB) in the sheep are reported in the present study. Furthermore, the first observation for Kappa casein patterns of Awassi sheep breed in Babylon city, Iraq was reported by the present paper. In addition, the population of kappa casein gene with AB genotype was the best choice for good fat and protein percentage of milk composition in the breed is previous reported.